Geometry or Algebra or Calculus?

Geometry Level 3

Given x , y , z x,y,z are nonnegative real values, such that x + y + z = 3 x + y + z = 3 , find the maximum value of 4 x y + 8 y z + 6 x z 4xy + 8yz + 6xz .

Challenge: \text{Challenge:} Solve this problem without any calculus.


The answer is 18.7826.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Pi Han Goh
Mar 28, 2021

Substitute z = 3 x y z = 3-x-y into the expression in question yields F : = 8 y 2 + 24 y 10 x y 6 x 2 + 18 x . F := -8y^2 + 24y - 10xy - 6x^2 + 18x .

By completing the square , F = 8 y 2 + 24 y 10 x y 6 x 2 + 18 x 0 = 2 ( 4 y 2 12 y + 5 x y ) 6 x 2 + 18 x 0 = 2 [ ( 2 y 3 + 5 4 x ) 2 9 + 15 2 x 25 16 x 2 ] 6 x 2 + 18 x 0 = 2 ( 2 y + 5 4 x 3 ) 2 23 8 ( x 2 24 23 x 144 23 ) 0 = 2 ( 2 y + 5 4 x 3 ) 2 23 8 [ ( x 12 23 ) 2 1 2 2 2 3 2 144 23 ] 0 = 2 ( 2 y + 5 4 x 3 ) 2 0 23 8 ( x 12 23 ) 2 0 + 432 23 432 23 18.783 \begin{array} { r c l} F &=& -8y^2 + 24y - 10xy - 6x^2 + 18x \\ \phantom 0 \\ &=& -2(4y^2 - 12y + 5xy) - 6x^2 + 18x \\ \phantom 0 \\ &=& -2 \bigg [ \left(2y - 3 + \dfrac54 x \right)^2 - 9 + \dfrac{15}2 x - \dfrac{25}{16}x^2 \bigg ] - 6x^2 + 18x \\ \phantom 0 \\ &=& -2\left(2y + \dfrac54 x - 3\right)^2 - \dfrac{23}8 \left(x^2 - \dfrac{24}{23}x - \dfrac{144}{23} \right) \\ \phantom 0 \\ &=& -2\left(2y + \dfrac54 x - 3\right)^2 - \dfrac{23}8 \bigg [ \left( x - \dfrac{12}{23}\right)^2 - \dfrac{12^2}{23^2} - \dfrac{144}{23} \bigg ] \\ \phantom 0 \\ &=& -2\underbrace{\left(2y + \dfrac54 x - 3\right)^2}_{\geqslant \, 0} - \dfrac{23}{8} \underbrace{\left( x - \dfrac{12}{23}\right)^2}_{\geqslant \, 0 } + \dfrac{432}{23} \leqslant \dfrac{432}{23} \approx \boxed{18.783} \end{array}

The maximum occurs when 2 y 5 4 x 3 = x 12 23 = 0 ( x , y , z ) = ( 12 23 , 27 23 , 30 23 ) . 2y - \frac54x -3 = x - \frac{12}{23} = 0 \hspace{10pt} \Leftrightarrow \hspace{10pt} (x,y,z) = \left( \dfrac{12}{23}, \dfrac{27}{23}, \dfrac{30}{23} \right) .

You're Da Man when it comes to Completing-the -Square, Pi Han!

tom engelsman - 2 months, 2 weeks ago

Log in to reply

The true algebra master is here!

Michael Huang - 2 months, 2 weeks ago

Log in to reply

THANKS FOR THE COMPLIMENTS! THANKS FOR THE COMPLIMENTS!

Pi Han Goh - 2 months, 2 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...